Effects of patient-controlled analgesia with hydromorphone or sufentanil on postoperative pulmonary complications in patients undergoing thoracic surgery: a quasi-experimental study - Guangming Yan (BMC Anesthesiology, 2018)
Abstract Objective To compare the analgesic effects of patient-controlled intravenous analgesia (PCA) with hydromorphone and sufentanil after thoracic surgery on postoperative pulmonary complications (PPCs). Methods A total of 142 patients who were scheduled for thoracic surgery were randomly allocated to receive PCA with hydromorphone (group A: experimental group): hydromorphone 0.2 mg/kg + dezocine 0.5 mg/kg + ramosetron 0.6 mg diluted with normal saline to 200 mL; or with sufentanil (group B: control group): sufentanil 3.0μg/kg + dezocine 0.5 mg/kg + ramosetron 0.6 mg diluted with normal saline to 200 mL. The parameters of intravenous analgesia pump were set as background dose 4 ml/h, PCA dose 1 mL, locking time 15 min. Pain NRS (numerical rating scale), Ramsay sedation score, nausea or vomiting score were evaluated at 0 h, 6 h, 12 h, 24 h, 48 h after operation. The cases of PPCs (atelectasis, pulmonary infection, respiratory failure), CRP (C-reaction protein) and inflammatory cells (white cell count and percentage of neutrophils) and blood gas analysis at 12 h after operation, length of ICU and postoperative stay were recorded for each patient. Results Data of 136 patients were analyzed. Compared with group B (4[IQR:2,2]), the pain NRS in group A (2[IQR:4,4]) was significantly lower at 6 h after operation (P = 0.000). The CRP in group A (69.79 ± 32.13 mg/L) were lower than group B (76.76 ± 43.42 mg/L) after operation, but the difference was not significant (P = 0.427). No difference of nausea or vomiting was found between group A (7.3%) and group B (5.8%) postoperatively (P = 0.999). The PPCs were happened in 11 patients in group A (16.2%) and 22 patients in group B (32.4%) and the difference between two groups was significant (P = 0.027). Seven patients in group A (10.3%) and eighteen patients in group B (26.5%) had clinical evidence of pneumonia and the difference between two groups was significant (P = 0.014). The length of ICU and postoperative stay in group A were 2.73 h and 1.82 days less than group B respectively but the differences were not significant (P = 0.234, P = 0.186 respectively). Conclusion Compared with sufentanil, hydromorphone may provide better postoperative analgesic effect with less pulmonary complications for patients undergoing thoracic surgery, and it may accelerate patients’ rehabilitation. Trial registration Randomized Controlled Trials ChiCTR1800014282c. Registered 3 January 2018.